A Retrospective Study: Epidemiology, Onset, and Duration of Erythema Nodosum Leprosum in Surabaya, Indonesia - Fransisca, Cindy; Zulkarnain, Iskandar; Ervianti, Evy; Damayanti, Damayanti; Sari, Maylita; Budiono, Budiono; Alinda, Medhi Denisa; Kusumaputra, Bagus Haryo; Prakoeswa, Cita Rosita Sigit; Listiawan, Muhammad Yulianto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Erythema nodosum leprosum (ENL) has a chronic and recurrent nature which could reduce patient's quality of life in addition to the onset of ENL that occurs before, during, or after multidrug treatment, further emphasizing the importance of regular control and education.Purpose:This study aimed to evaluate the epidemiology, onset, duration, and recurrence of ENL. Methods:Data from medical records were obtained for a 3-year retrospective study of multibacillary leprosy patients at the Leprosy Division of the Dermatology and Venereology Outpatient Department, Dr. Soetomo General Hospital Surabaya, with a minimum of 2–5 years follow-up period.Result:The prevalence of  ENL continued to increase almost every year especially in 2017 (32% in 2015; 32% in 2016; and 36% in 2017). ENL most often occurs during the first year of multi-drug therapy (MDT) administration followed by after the release from treatment (RFT) with the latest onset occurring 4 years after RFT. The majority of patients experienced chronic and recurrent reactions with the longest reactions lasting up to 4.5 years (55 months). Conclusion:Knowledge about the onset, duration, and recurrences of ENL are essential, and strict supervision for routine control shall be encouraged to increase the patients' compliance so as to increase their quality of life.